Knowledge and Awareness for the Early Detection and Intervention of Short Stature among Families in Qassim Region 2021–2022: A Cross-Sectional study - Alharbi, Mariam Saleh; Alatni, Rufaydah Ibrahim; Alhammad, Rana Abdullah; Alotaibi, Mzoun Abdulaziz; Alhatlani, Anwar Hamad; Alshaya, Ream Humaidan; Alharbi, Abdulaziz O. (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Short stature is a common reason for the referral of children to endocrinology clinics. A study in Saudi Arabia recorded a relatively high frequency of short stature among children and adolescents. This condition is multifactorial and can be influenced by genetic factors, environmental factors, or endocrine diseases. Early detection and intervention are crucial steps in the long-term outcomes and benefits. Aim: To evaluate the knowledge and awareness for the early detection and intervention of short stature. Methods: A cross-sectional study utilizing a representative random cluster sample of 384 participants living in various cities in the Qassim region, including Buraydah, Unaizah, Alrass, and Riyadh Al Khabra, and in places outside the central region from October 2021 to March 2022. To achieve our goals, we used a self-administered questionnaire that evaluated knowledge and awareness for the timely identification and intervention of short stature among families in the Qassim region. Results: We received 469 surveys. The overall mean knowledge score was 2.04 (SD 0.92), with poor and good levels of knowledge identified among 68.4% and 31.6%, respectively. Higher knowledge scores were associated with being married, having children, and having a family history of short stature. Conclusion: Based on our data, we conclude that the majority of Qassimi families have poor knowledge about the early detection and intervention of short stature.